Unique band structure enhanced visible light photocatalytic activity of phosphorus-doped BiOI hierarchical microspheres. Issue 58 (20th July 2017) - Ma, Fen-Qiang; Yao, Jing-Wen; Zhang, Yan-Feng; Wei, Yu
Abstract : In this article, phosphorus (P)-doped BiOI hierarchical microspheres were prepared via a facile hydrolytic method at room temperature. Abstract : In this article, phosphorus (P)-doped BiOI hierarchical microspheres were prepared via a facile hydrolytic method at room temperature. The morphology and structure of the samples were characterized by using X-ray powder diffraction, scanning electron microscopy, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, nitrogen sorption diffraction, photoluminescence spectroscopy and UV-visible diffuse spectroscopy. Based on these results, it was concluded that the P doping was beneficial to forming uniform hierarchical microspheres, which consisted of numerous two-dimensional nanosheets with a thickness in the range of 30–40 nm. It is believed that the phosphorus species had been doped into the lattice of BiOI and formed Bi–O–P bonds. Based on this fascinating characterization, the photocatalytic activity of P-doped BiOI was evidently improved, and the photocatalytic activity of the 4% P-BiOI sample for degradation of RhB is almost 2.6 times as high as pure BiOI in the case of visible light irradiation. Furthermore, the P doping could not only increase the width of the valence band but also raise the conduction band minimum, which led to the more efficient separation capacity of photogenerated carriers, the higher mobility of the resulting holes and the greater concentration of superoxide ions. In addition, the possible photocatalytic mechanism of P-doped BiOI microspheres for degrading Rhodamine B dye was proposed.